1997
DOI: 10.1002/vnl.10162
|View full text |Cite
|
Sign up to set email alerts
|

Successful extrusion of small diameter CPVC pipe

Abstract: Chlorinated polyvinylchloride (CPVC) pipe is a rapidly growing market, especially 25.4 mm (1") pipe and smaller. Extrusion of CPVC pipe presents a greater challenge than PVC, because CPVC has less heat stability and higher viscosity. However, CPVC has good physical properties, particularly with respect to heat, and can be used to make hot water pipe. This paper discusses some of the basic factors involved in screw and pipe head design for CPVC extrusion, and gives some examples of successful applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Therefore, the CPVC is receiving more and more attention and has been widely applied in industrial and civil fields due to its superior physico-chemical properties, [4] such as thermal stability, [5] corrosion resistance, [6,7] and flame resistance. [8,9] There are three methods for chlorination: suspension, gas-solid, and solution. [10][11][12] The aqueous suspension was performed in high temperature and high pressure in the presence of an oxidizing agent, which reduces the molecular weight, thereby diminishing the mechanical properties of the product.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the CPVC is receiving more and more attention and has been widely applied in industrial and civil fields due to its superior physico-chemical properties, [4] such as thermal stability, [5] corrosion resistance, [6,7] and flame resistance. [8,9] There are three methods for chlorination: suspension, gas-solid, and solution. [10][11][12] The aqueous suspension was performed in high temperature and high pressure in the presence of an oxidizing agent, which reduces the molecular weight, thereby diminishing the mechanical properties of the product.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorinated poly(vinyl chloride) (CPVC) is one of the most widely used engineering materials because of its better mechanical properties and lower flammability . Nevertheless, it has been reported that CPVC is more difficult to process. Moreover, it has poor toughness, which limits its application.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known to have a higher softening temperature, higher heat deflection temperature, lower flammability, lower smoke properties, and chemical inertness than conventional polyvinylchloride (PVC). However, in the literature , it has been reported that CPVC is more difficult to process. Moreover, it has poor impact strength, which limits the application of CPVC.…”
Section: Introductionmentioning
confidence: 99%